GAMBARAN KESEHATAN FISIK PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Syahrizal; Wahyu Agustina (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Chronic kidney failure is a progressive, irreversible kidney function, fluid and electrolyte imbalance causing retention of urea and other nitrogenous waste in the blood. Hemodialysis is a method of flowing blood into a dialyzer (artificial kidney tube). While physical health is a condition of the human body where every organ or part of the human body functions well, while patients with chronic kidney failure do not support. This study uses a Cross Sectional research design with a